2019
DOI: 10.15252/embj.2019103397
|View full text |Cite
|
Sign up to set email alerts
|

Beyond inflammasomes: emerging function of gasdermins during apoptosis and NETosis

Abstract: Programmed cell death is a key mechanism involved in several biological processes ranging from development and homeostasis to immunity, where it promotes the removal of stressed, damaged, malignant or infected cells. Abnormalities in the pathways leading to initiation of cell death or removal of dead cells are consequently associated with a range of human diseases including infections, autoinflammatory disease, neurodegenerative disease and cancer. Apoptosis, pyroptosis and NETosis are three well-studied modes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 94 publications
(154 reference statements)
2
76
0
Order By: Relevance
“…Induction of the inflammasome complex activates caspase-1 and facilitates formation of GSDMD, which further promotes secretion of pro-inflammation cytokines IL-1β and IL-18 from the pore of the cell membrane resulting in inflammation-associated pyroptotic cell death [5,35]. It has been reported that activation of inflammasome induces apoptosis [36]. Apoptosis is a highly mediated subtype of cell death, which is particularly linked to the cerebral reperfusion phase.…”
Section: Agingmentioning
confidence: 99%
“…Induction of the inflammasome complex activates caspase-1 and facilitates formation of GSDMD, which further promotes secretion of pro-inflammation cytokines IL-1β and IL-18 from the pore of the cell membrane resulting in inflammation-associated pyroptotic cell death [5,35]. It has been reported that activation of inflammasome induces apoptosis [36]. Apoptosis is a highly mediated subtype of cell death, which is particularly linked to the cerebral reperfusion phase.…”
Section: Agingmentioning
confidence: 99%
“…Inflammasomes process the pro-inflammatory cytokines IL-1β and IL-18 into their active forms ( de Rivero Vaccari et al, 2014 ; de Rivero Vaccari et al, 2016 ). In neutrophils, activated caspase-1 or caspase-11 cleave gasdermin-D (GSDM-D), which leads to pyroptosis and NETosis ( Chen et al, 2018 ; Chen et al, 2020 ). Moreover, NETs are downstream of neutrophil inflammasome activation ( Chen et al, 2018 ; Sollberger et al, 2018 ; Westerterp et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gasdermin D (GSDMD) is a pore-forming protein that has emerged as an important player during different modes of cell death including pyroptosis, apoptosis, and NETosis ( 1 ). GSDMD consists of a cytotoxic N-terminal domain (GSDMD NT ) and a repressor C-terminal domain (GSDMD CT ) that is connected by a flexible linker ( 2 ).…”
Section: Introductionmentioning
confidence: 99%